2023
DOI: 10.1039/d3ta04472f
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve the photocatalytic performance of covalent triazine frameworks

Yubing Liu,
Hao Wu,
Qian Wang

Abstract: Covalent triazine frameworks (CTFs) have emerged as a prominent group of organic semiconductors, distinguishing themselves from covalent organic frameworks (COFs) for their applications in photocatalysis. Their unique features, such as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 221 publications
0
4
0
Order By: Relevance
“…16,17,36,37 While most photocatalytic studies focus on boosting water splitting, [38][39][40] hydrogen production [41][42][43][44] or carbon dioxide reduction, [45][46][47] only a few reports consider the potential of tailor-made CTF photocatalysts for metal-free organosynthesis. [48][49][50][51][52][53][54][55] Especially, CTF's ability to activate molecular oxygen makes it promising for benign oxidations. 35 Zhang et al demonstrated the successful oxidation of several benzyl alcohols to the corresponding aldehydes or ketones with a thiophene based CTF.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,36,37 While most photocatalytic studies focus on boosting water splitting, [38][39][40] hydrogen production [41][42][43][44] or carbon dioxide reduction, [45][46][47] only a few reports consider the potential of tailor-made CTF photocatalysts for metal-free organosynthesis. [48][49][50][51][52][53][54][55] Especially, CTF's ability to activate molecular oxygen makes it promising for benign oxidations. 35 Zhang et al demonstrated the successful oxidation of several benzyl alcohols to the corresponding aldehydes or ketones with a thiophene based CTF.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, it can increase the adsorption of visible light, reduce the recombination of free charges, enhance the transport mobility of carriers, and ultimately improve the photocatalytic performance. 10–17…”
Section: Introductionmentioning
confidence: 99%
“…2,4,6-Tris(4-formylphenyl)-1,3,5-triazine (TFPT), as another functional monomer, a stable conjugate system exists between C and N rings in its structure. [14] By adjusting the stoichiometric ratio of aldehydes and amines, the π-conjugated system of the obtained material can be optimized, which can change the molecular structure and regulate the energy band structure, thereby improving the photocatalytic activity. Two precursors, TFPT and OAPS, were bonded through C=N to obtain a three-dimensional network structure with an extended π-electron conjugated system, achieving synchronous control of the electronic and topological structure of the catalyst.…”
Section: Introductionmentioning
confidence: 99%